2014
DOI: 10.4274/tjod.94759
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mixed type endometrial carcinoma

Abstract: Amaç: Bu çalışmanın amacı miks tip endometrium kanserinde görülen lokal cerrahi-patolojik faktörler ve bu faktörlerin hücre tipleri ile olan ilişkisini incelemektir. Gereç ve Yöntemler: Ocak 1993-Mayıs 2013 yılları arasında nihai tanısı miks hücre tipi endometrium kanseri olan 33 olguya ait veriler retrospektif olarak değerlendirildi. Bulgular: Endometrium kanseri tanısı alıp tedavisi yapılmış 1640 hastanın 33'ü (%2) miks hücre tipine sahipti. Hasta grubunun ortalama yaşı 60 yıldı. 2009 FIGO evreleme sistemine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In this study, the ratio of metastases to the omentum in the group of patients who had an omentectomy was 5.9%. It was 9.1% in our previous study evaluating mixed-type endometrial carcinoma (19). Similarly, the ratio of omental metastasis in endometrial cancer was reported between 2.4% and 8.3% (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, the ratio of metastases to the omentum in the group of patients who had an omentectomy was 5.9%. It was 9.1% in our previous study evaluating mixed-type endometrial carcinoma (19). Similarly, the ratio of omental metastasis in endometrial cancer was reported between 2.4% and 8.3% (8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 98%
“…These rates differ with tumor histopathology and stage. A study evaluating the mixed histologic type was reported omental metastasis rates as 9.1%, whereas it was 18.7% in serous carcinoma [19,20]. In early-stage serous carcinomas, it is only 5.1-9.8% [21,22].…”
Section: Discussionmentioning
confidence: 99%